Investigation of the joining of acrylic by low power CO2 laser - Tiong, Chiong Chii (2013)
In the last few decades, the technology of welding has been improved and there are several types of welding technology being invented. Carbon dioxide (〖CO〗_2) laser welding is one of the new technologies that have been playing an important role in this era. In this project, the optimum parameter of the welding of acrylic by low power 〖CO〗_2 laser is studied. Three main parameters are studied in this project which is stand-off distance, welding speed and the number of pass. The power is constant which is 75 Watt. These three main parameters are grouped by using the Taguchi Method in Minitab Software. The grouped parameter is then investigated and the tensile strength and micro-bubble size of each group is tested and recorded in table form. The Analysis of variance (ANOVA) table is prepared and the ranking of each parameter is investigated. Several graphs are plotted in order to find the relationship between the tensile strength and the micro-bubble size. The best parameter is determined. In conclusion, the smaller the micro-bubble size, the lower the tensile strength until it reached optimum point. After the optimum point, the smaller the micro-bubble size, the higher the tensile strength will be.